Factors Associated with Disclosure of Intimate Partner Violence among Women in Lagos, Nigeria - Okenwa, Leah; Lawoko, Stephen; Jansson, Bjarne (Injury and Violence, 2009)
Though the prevalence of Intimate Partner Violence (IPV) remains high in less developed countries, data suggest that these figures may represent an underestimation considering that many women are unwilling to disclose abuse. This paper aims to determine women’s willingness to report abuse, factors determining willingness to disclose IPV, and to whom such disclosure is made. Methods: A total of 911 women visiting reproductive health facility responded to the questionnaire, and the collected data was analyzed using multivariate analysis. Results: About 54% (n=443) of the participating women reported that would not disclose IPV. Among those willing to disclose abuse, 68% (n=221) would opt to disclose to close relatives in contrast to 37% (n=103) who would disclose to some form of institutions (i.e. religious leaders, law enforcement officers). Ethnicity, woman’s own use of alcohol and autonomy in decision making such as having a say on household purchases, money use and visitation, independently predicted willingness to disclose IPV.
Keywords: Intimate partner violence; Women; Nigeria; Willingness to disclose IPV; Family; Police